Antioxidant Properties of Kaffir Lime Oil as Affected by Hydrodistillation Process - Wulandari W.Y., Darmadji, P & Kurniawati, L (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
Kaffir lime oil is essential oil from kaffir lime leaves (Citrus hystrix. DC). That essential oilpossesses some important bioactivities such as antioxidant, antileukemic, antitussive,antihemorrhage, antioxidative stress properties, and antibacterial properties. Nowdays,essential oil of kaffir lime is in demand as a fragrance in the food, perfumery and cosmeticindustries our present study investigated the effect of leaves treatment by hydrodisstillationprocess on phenolic compounds and antioxidant properties as well as volatile compounds ofkaffir lime leaf. The results showed milling provided the highest values of total phenolic(23.15 mg/GAE/g) and total flavonoid contents (12.85 mg/RE/g) along with antioxidantactivities determined by in vitro DPPH assays. Our findings suggest that different treatmentof leafs before hydrodisttilation process caused various effect on the phenolic compoundsand antioxidant properties of kaffir lime oil.Keywords : kaffir lime oil, phenolics, flavonoids, hydrodistillation